Endoglin Expression and the Level of Tgf-Î’ Are Increased In the Placental Tissue and Correlated with Low Fetal Weight in Malaria Infected Mice - sujarot dwi sasmito; Adilah Ulfiati; Ardhian Wardana; Fitriana Nugraheni; Nur Fahma Pradiptasari; Zakiyah Zulaifa; Eviana Norahmawati; Teguh Wahju Sardjono; Loeki Enggar Fitri (Journal of Tropical Life Science, 2015)
Malaria infection during pregnancy can cause accumulation of infected-red blood cells in placental intervillous space and induces placental tissue inflammation and hypoxia. This condition triggers endoglin expression, and release of soluble endoglin which can interfere TGF-Î² binding to its receptor. The aim of this study was to investigate the correlation between placental endoglin expression and TGF-Î² level with low fetal weight (LFW) in malaria-infected mice. Nine pregnant mice infected with Plasmodium berghei on the day 9th post mating (malaria infected group) and eight normal pregnant mice (non-infected group) were used in this study. The mice were sacrificed on the day 18th post mating, and all fetal body weights were measured by analytical scale. Enzyme Link Immunosorbent Assay (ELISA) was done to determine the level of placental TGF-Î² while immunohistochemical staining was performed to examine endoglin expression in placental tissue. The mean of fetal body weights of malaria infected group was significantly lower than non-infected group (p=0,002), while the expression of placental endoglin in malaria infected group was significantly higher than non-infected group (p=0.003). The level of placental TGF-Î² in malaria infected group was also higher than non-infected group but the difference was not significant (p=0.064). Pearson correlation test showed that there were significant negative correlations between fetal body weights with the level of placental TGF-Î² (p=0.017, r=-0.568) and the expression of placental endoglin (p=0.002, r=-0.694). Malaria infection in pregnant mice will increase both TGF- Î² and endoglin in placenta tissue and correlate with low fetal weight.Â Â Â